(untitled) (Journal of the College of Basic Education, 2023)
For every event in life there must be preliminary precursors that lead to its emergence, emergence, spread, acceptance or approval. It was rejected by the people to whom the event was directed. Islam is a great event in the history of mankind. Where a change occurred in the lives of Arabs and Muslims, and the will of God, the Almighty, required preparing the minds of people to accept it and act upon it and spread it among people so that a life of unity, love and cooperation prevails, and this requires the rule of The collective spirit to be a good cradle for what Islam seeks; With these meanings calling for the unification of the tribes of